Response of the tomato crop (Solanum lycopersicum L.) to the application of QuitoMax® in salinity conditions (Research, Society and Development, 2022)
The effect of QuitoMax® on the behavior of tomato plants of the Claudia and Amalia varieties under saline stress conditions was studied. The experiment was carried out in the municipality of Cauto Cristo, province of Granma, from October/2017 to March/2018, in a soil classified as saline sodium (CE 4 dS m-1). The experimental design used was a random block design, with a factorial arrangement, replicating each variant four times. The biostimulant was applied 12 days after transplantation (DAT) at a rate of 300 and 400 mg ha-1 and the control (zero application). Plant height, root length, number of fruits, number of bunches per plant, equatorial diameter, polar diameter and yield were evaluated at 45 DAT. The application of the biostimulant QuitoMax® increases the number of clusters per plant and the mass of tomato fruits under salinity conditions compared to the control. Agricultural yields were increased by 43% and 76%, as well as economic benefits by $1,653.93 ha-1 and $3,418.08 ha-1 compared to the control, for cultivars Amalia and Claudia, respectively, grown under salinity conditions. The best results were obtained when applying the dose of 300 mg ha-1 of QuitoMax®.